Influence of hard cold working on microstructure and properties of annealing copper tubes - Ivanov S.; Marković Desimir (Journal of Mining and Metallurgy. Section B: Metallurgy)
This work gives results of influence of temperature and deformation degree on changes in the metal grain growth of drawn copper tubes, because this mutual dependence was observed. Copper tubes samples, chemical content of 99,97 % Cu and 0,024 % P, were exposed to recrystallized annealing after drawing. The annealing was carried out at temperatures of 573, 623, 673, 723, 773, 823 and 873 K, for 60 minutes, in laboratory conditions. Investigation results show that after drawing with high cold deformation degree (96 - 99 %), the annealing leads to the changes in the continuous grain growth with increased temperature. The smaller grain size appears at 823 K in comparison with the lower annealing temperature. Annealing has influence on mechanical characteristics of tested samples and during drawing of copper tubes these characteristics are adequately changed: with regard to the annealing at the 773 K, the characteristics of strength and plasticity increase as a result of decreased grain size. The increase of annealing temperature to 873 K leads to the increased grain size and decreased values of strength and plasticity characteristics.